HUBUNGAN HASIL BELAJAR MATA PELAJARAN MATEMATIKA DAN FISIKA DENGAN PENGETAHUAN SISWA PADA MATA PELAJARAN PEMPROGRAMAN DASAR DI SMK NEGERI 7 TAKALAR - Dian Atmasani; Muhammad Yahya; Muhammad Farid (UNM Journal of Technology and Vocational, 2021)
This study aims to determine the description of student learning outcomes in Mathematics, Physics and Basic Programming subjects at SMK Negeri 7 Takalar and to determine the relationship between student learning outcomes in Mathematics and Physics subjects with Student Knowledge in Basic Programming subjects. Ex-post facto research method. The total population is 210 people and the sample is 63 people taken at random proportionally. Data collection using documentation and tests. Hypothesis testing is carried out after conducting the analysis prerequisite test. The results of this study indicate that: (1) student learning outcomes in Mathematics are in the "good" criteria. (2) student learning outcomes in Physics subjects are in the "good" criteria. (3) student learning outcomes in Basic Programming subjects are in the "good" criteria. (4) there is a relationship between learning outcomes in Mathematics with students' knowledge of Basic Programming subjects of R=0.418 and the value of Sig. of 0.000 < 0.05 with a contribution of 17.5%, (5) there is a relationship between learning outcomes in Physics subjects with student knowledge in Basic Programming subjects of R = 0.468 and the value of Sig. of 0.000 < 0.05 with a contribution of 21.9%, (6) there is a joint relationship with students' knowledge of Basic Programming subjects of R = 0.538 and the value of Sig. of 0.000 < 0.05 with a contribution of 28.9%. So the research hypothesis is accepted.